KETAHANAN ALAMI KAYU HIBRID AKASIA (Acacia mangium × A. auriculiformis) TERHADAP SERANGAN RAYAP KAYU KERING (Cryptotermes cynocephalus Light.) - Fatma Zohra; Sri Sunarti; Tomy Listyanto (Jurnal Pemuliaan Tanaman Hutan, 2021)
Development of Acacia hybrid is important to be done due to their superiority such as high productivity, good wood quality, more tolerance to pest/disease and adaptive to marginal sites, although its wood durability to wood-destroyer organism attacks is still unknown yet. This study aimed to observe the wood natural durability of Acacia hybrid to drywood termites (Cryptotermes cynocephalus Light.) attack. The wood samples used were taken from 6 years old trees of Acacia hybrid in Wonogiri, Central Java. The experimental design used is completely randomized design using two factors, axial and radial of wood section with the number of trees as replication. Parameters measured were extractive content, termite mortality and wood mass loss. The results showed that the axial section of wood significantly affected the wood extractive content at the level of 0.01, while termite mortality and the mass loss of wood were not significantly affected by the wood section. The largest average percentages of termite mortality and mass loss of wood found on the middle of wood section (96.67%) and near the bark (1.14%) respectively. Based on this result, the Acacia hybrid wood is categorized as very durable wood and potential to be developed as raw material for solid wood-based industries.